Agama dan Perubahan Sosial - Nesia Mu’asyara; Atik Herawati; Hendika Prayoga; Putri Putri; M. Sopyan; Andini Putri Pangestika; Muldiyansyah Muldiyansyah; Abdul Aziz; Robi Adil (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Religion has a very important role in human life on this earth. Religion functions as a harmonizer of life. In the context of social change, religion directs change for the better. Religious teachings have a great influence in unifying people's perceptions of life. The presence of religion functions as a